Feasibility and readiness to implement Robson classification to monitor caesarean sections in public hospitals in Myanmar: Formative research. - Kyaw Lwin Show; Thae Maung Maung; Aung Pyae Phyo; Kyaw Thet Aung; Chetta Ngamjarus; Nyein Su Aye; Özge Tunçalp; Ana Pilar Betrán; Saw Kler Ku; Pisake Lumbiganon; Khaing Nwe Tin; Nwe Oo Mon; et al. (Public Library of Science (PLoS), 2023)
Recent years have demonstrated an increase in caesarean section (CS) in most countries worldwide with considerable concern for the potential consequences. In 2015, WHO proposed the use of Robson classification as a global standard for assessing, monitoring and comparing CS rates. Currently, there is no standardized method to assess CS in Myanmar. The aim of this study was to explore health provider's perceptions about the feasibility, acceptability and readiness to implement the Robson classification in public hospitals across Myanmar. Ten maternities were purposively chosen, including all five teaching hospitals (tertiary referral hospital-level) affiliated to each medical university in Myanmar, which provide maternal and newborn care services, and district/township hospitals. Face-to-face in-depth interviews (IDI) with healthcare providers and facility administrators were conducted using semi-structured discussion guides. Facility and medical records systems were also assessed. We used the thematic analysis approach and Atlas.ti qualitative analysis software. A total of 67 IDIs were conducted. Most participants had willingness to implement Robson classification if there were sufficient human resources and training. Limited human resources, heavy workloads, and infrastructure resources were the major challenges described that may hinder implementation. The focal person for data entry, analysis, or reporting could be differed according to the level of facility, availability of human resources, and ability to understand medical terms and statistics. The respondents mentioned the important role of policy enforcement for the sustainability of data collection, interpretation and feedback. The optimal review interval period could therefore differ according to the availability of responsible persons, and the number of births. However, setting a fixed schedule according to the specific hospital for continuous monitoring of CS rate is required. In Myanmar, implementation of Robson classification is feasible while key barriers mainly related to human resource and training must be addressed to sustain.